Acute morphine injection persistently affects the electrophysiological characteristics of rat locus coeruleus neurons. (31st January 2023) - Farahani, Fatemeh; Pachenari, Narges; Mohammad Ahmadi-Soleimani, S.; Azizi, Hossein; Semnanian, Saeed
Graphical abstract: Highlights: Prolonged effect of acute morphine treatment on LC neurons was studied. Acute morphine exposure decreased firing rate of LC neurons after 24 h. In LC, the rise and decay slopes of action potential were decreased and half-width was increased by morphine. Morphine injection did not affect first spike latency and rheobase current in LC neurons. Morphine injection prevented the excitatory effect of OXA on postsynaptic currents of LC neurons. Abstract: Administration of morphine is associated with critical complications in clinic which primarily includes the development of dependence and tolerance even following a single dose (acute) exposure. Behavioral and electrophysiological studies support the significant role of locus coeruleus (LC) neurons in tolerance and dependence following chronic morphine exposure. The current study was designed to explore the electrophysiological properties of the LC neurons following acute morphine exposure. In-vitro whole-cell patch-clamp recordings were performed in LC neurons 24 h after intraperitoneal morphine injection. Acute morphine injection significantly decreased the spontaneous firing rate of LC neurons, the rising and decay slopes of action potentials, and consequently increased the action potential duration. In addition, morphine treatment did not alter the rheobase current and first spike latency while affected the inhibitory postsynaptic currents elicited in response to orexin-A. In fact, single morphine exposure could inhibit the disinhibitory effect of orexin-A on LC neurons.